Weight stigma in physiotherapy practice: Patient perceptions of interactions with physiotherapists. Issue 6 (December 2015) - Setchell, Jenny; Watson, Bernadette; Jones, Liz; Gard, Michael
Abstract: Background: Weight management is increasingly considered part of physiotherapists' scope of practice in order to improve patient outcomes by, for example, reducing load on joints, or improving chronic pain. However, interactions with patients involving weight may result in patient perceptions of negative judgement from health professionals, which can result in poorer health outcomes. How physiotherapist/patient interactions involving weight are perceived by patients has not yet been investigated. Objectives: To explore patients' perceptions of interactions with physiotherapists that involved weight, and investigate how these perceptions may inform physiotherapy practice. Design: Face-to-face interviews with physiotherapy patients, with follow up interviews conducted by telephone. Data were analysed thematically. Method: First interviews were held in a physiotherapy practice with follow up interviews conducted two weeks later. Interviews were audio recorded, transcribed and analysed using an inductive thematic method established by Braun and Clarke. Findings: Thirty interviews with 15 patients were analysed. Four main themes relevant to weight were identified: 1) perceptions of being 'in physiotherapy' including pre-conceptions, the physical environment, and exposing the body, 2) emphasis placed on weight in physiotherapy interactions, 3) communication styles, and 4) judgement perception. Conclusion: Some patients perceived negative weight judgements from elements of physiotherapy interactions and environments. Physiotherapists need to be aware of this perception because it may result in poorer patient outcomes and patients avoiding physiotherapy appointments. The results suggest strategies to counteract weight stigma include: adjusting the physical environment of the clinic, portraying an understanding of complex determinants of weight, and employing collaborative, non-judgemental communication styles. Highlights: Patients perceived negative weight judgements from some physiotherapy interactions. This may result in poorer patient outcomes and avoidance of physiotherapy. Awareness of this means that physiotherapists can be more sensitive to this issue. Suggested strategies include collaborative communication, avoiding blaming patients. Also not talking weight when patients are undressed and minimising use of mirrors.